Voluntary Migration in Ethiopia : In Search for Work and Better Opportunities - Wieser, Christina; Mekonnen, Berhe; Cardona-Sosa, Lina; Abubakar, Aisha (World Bank, Washington, DC, 2022)
People migrate both within and between countries to improve their lives and the lives of families left back home. Evidence is growing on the significant returns to voluntary internal and international migration. Wage differentials incentivize people to cross borders and work abroad. Despite positive welfare effects, internal migration can also strain destination communities, particularly urban areas, which can contribute to negative social externalities. The benefits of internal and international labor migration, especially increasing household incomes and reducing poverty, are likely to outweigh costs. Policies in Ethiopia have focused on the negative aspects of migration, but perceptions are changing. This report expands the understanding of voluntary economic migration in Ethiopia. This report presents a comprehensive picture on migration in Ethiopia by synthesizing previous research and complementing existing evidence with new analysis using more recent data, including the latest available 2021 labor force and migration survey (LMS). This report is structured around two broad sections, which aim to provide a comprehensive picture of voluntary internal and international migration in Ethiopia, as well as a section highlighting broad policy implications. Chapter one gives introduction. Chapter two provides an overview of migration in Ethiopia and the latest trends on migration. Chapter three discusses migration motives and effects. Chapter four highlights policy directions to maximize the benefit of migration while minimizing the costs.